Analysis on impact of energy efficient techniques to enhance the building performance. Issue 4 (August 2020) - Sharma, Prerna; Prasathkumar, V.R.; Senthil Kumar, R.; Krishnaraj, L.
Abstract: A substantial share of energy goes into building air-conditioning under harsh climatic conditions. The climate control load could be decreased by several means; the proper structure and choice of the building envelope and its components are noteworthy among them. Due to the growing global warming and energy crisis, energy analysis is becoming a major factor to be considered in the industry these days. During the design process, power forecasting is on the rise use and alternative energy is considered as conservation measures and considerations for creating a more energy-efficient building. To minimize the annual energy use and annual cost, the study of the commercial school building has been done by employing various alternatives in the conventional school building model. The different parameters taken for the study are (heating load, cooling load, orientation and lighting control). Analysed the alternative scenarios, and the findings were collected. Each case comparison is based on energy use and the annual cost. The result shows that from the combined use with Autodesk Revit and a Green Building Studio, the integrated energy analysis and design alternatives can provide more building with energy-efficient. The accuracy of the data can greatly affect the results obtained.